FIRM SPESIFIC FACTORS SEBAGAI DETERMINAN NILAI PERUSAHAAN SEBELUM DAN SELAMA PANDEMI COVID-19 - Putri, Dewi Santika; Hascaryani, Tyas Danarti (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2023)
The Covid-19 pandemic has affected investors' judgments in determining indicators to make investment decisions. This study analyzes firm specific factors that affect firm value before and during the Covid-19 pandemic in LQ-45 companies on 2018-2021. Firm specific factors are measured by leverage, profitability, liquidity, and company size. Meanwhile, firm value is measured by Price Earning Ratio (PER). The analytical method used is Panel Data Regression Analysis with the Covid-19 Pandemic as a Dummy variable. The results of this study indicate that company size and liquidity have a significant positive effect on firm value, the profitability and leverage variables show a significant negative effect on firm value before the Covid-19 pandemic. Meanwhile, during the Covid-19 pandemic, different results were obtained on the profitability variable, which had a significant positive effect and company size had no effect on firm value. And the Covid-19 pandemic variable has a significant negative effect on company value. This research becomes a reference for investors in determining indicators to make investment decisions and becomes the basis for companies to improve company performance.